Skrining Bakteri Asam Laktat Dan Khamir Potensial Proteolitik Ekstraseluler Dan Milk Clotting Activity Dari Getah Dan Fresh Cheese Pepaya (Carica papaya L.) - Aliifah, Felicia; Rustama, Mia Miranti; Putranto, Wendry Setiyadi (Unpad Press, 2023)
Fresh cheese is a type of cheese without a fermentation process which is formed due to the milk coagulation process using the enzyme rennin. The use of rennin can be replaced using protease enzymes produced from papaya fruit sap and microorganisms. Protease enzymes from microorganisms are more profitable because they are easy to produce and gow faster. This research was carried out by making fresh cheese using papaya sap coagulum and then isolating lactic acid bacteria and yeast which have proteolytic activity and milk clotting activity. This research method is exploratory descriptive. The results showed that the total amount of LAB from fresh cheese and papaya latex was 2.4x10 6CFU/g and 1.1x10 7CFU/ml respectively, and the total amount of yeast was 1.5x10 3CFU/g and 2.4x10 6CFU/ml. Candidate LAB isolates were found to have proteolytic activity with the highest to lowest Proteolytic Index values with isolate codes G4, G3, G5, and G1 of 1.7; 1.3; 1.08 and G1 was negative or < 0. Y1 yeast isolate had an IP of 1.36 and Y4 isolate was negative or < 0. The MCA values for isolates G4, G3, G5 and G1 were 267.2 SU/ml, 250.95 SU/ml, respectively. 156.8 SU/ml and 138.1 SU/ml and both yeast isolates could not coagulate milk. The four bacterial isolates found in this study did not belong to the LAB goup. Isolates G3 and G4 have characteristics that are almost similar to the genus Bacillus, while the two yeast isolates belong to the genus Pichia and Debaryomyces. So in this study no potential isolates were found to come from lactic acid bacteria or yeast.